Evaluation of core losses and temperature rise in a high frequency transformer and estimate the relative errors with FEM simulation - Hau, Nicholas Wee Kiat (Nanyang Technological University, 2021)
Evaluation of transformer losses has always been an active research area in power systems. Transformer losses result in thermal rise in the core, causing overheating and in worse cases, complete transformer failure. This report will focus on the research of high frequency transformer losses, calculation of transformer core losses and temperature rise, designing of simulation model in ANSYS Maxwell, simulation of core losses in ANSYS Maxwell, simulation of temperature rise in ANSYS AIM and analysis of the relative errors.